2013
DOI: 10.1364/ol.38.000697
|View full text |Cite
|
Sign up to set email alerts
|

Toward a downconversion source of positively spectrally correlated and decorrelated telecom photon pairs

Abstract: The frequency correlation (or decorrelation) of photon pairs is of great importance in long-range quantum communications and photonic quantum computing. We experimentally characterize a spontaneous parametric down conversion (SPDC) source, based on a β-Barium Borate (BBO) crystal cut for type-II phase matching at 1550 nm which emits photons with the positive or no spectral correlations. Our system employs a carefully designed detection method exploiting two InGaAs detectors.OCIS codes: 190.4410,300.6190,270,41… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Such a quantum state engineering method can be realized by considering the group-velocity-matched (GVM) condition in specific crystals at certain wavelengths [4][5][6]. Previous work in the field has shown that the GVM condition can be realized in several crystals, e.g., KDP crystal at 830 nm [1,2,7], periodically poled KTP crystal (PPKTP) at 1584 nm [5,8] and BBO crystal at 1514 nm [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Such a quantum state engineering method can be realized by considering the group-velocity-matched (GVM) condition in specific crystals at certain wavelengths [4][5][6]. Previous work in the field has shown that the GVM condition can be realized in several crystals, e.g., KDP crystal at 830 nm [1,2,7], periodically poled KTP crystal (PPKTP) at 1584 nm [5,8] and BBO crystal at 1514 nm [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Optical elements are dispersive and cause unwanted modification of the photons' temporal characteristics. The deteriorating dispersion effects can be reduced by using photon pairs that are spectrally narrow and feature appropriate spectral correlations [16][17][18].The spectra of SMF coupled photon pairs generated in SPDC process can be negatively [19,20], positively [16][17][18][21][22][23] or not correlated at all [24][25][26]. The effect of negative correlation originates from the energy conservation relation and is a consequence of pumping by a continuous wave (CW) laser.…”
mentioning
confidence: 99%
“…The spectral part of the pump can also be approximated by a Gaussian function with the characteristic spectral width 1/(2τ pump ). The spectral wave function then reads:(1) It has already been show experimentally [18] that the EPMF of the type II BBO crystal cut for telecom wavelength facilitates spectral correlation control. Tuning capabilities arise due to the variable pulse duration τ p of the pump laser and the variable collection optics which influences the characteristic width σ of the EPMF.…”
mentioning
confidence: 99%
“…We use a method similar to the one already used to reconstruct EPMF in Ref. [18]. The results are presented in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation